Control of root rot and wilt disease complex of some evergreen fruit transplants by using plant growth promoting rhizobacteria in the New Valley Governorate, Egypt - Abdel-Monaim, M. F.; EL-Morsi, M. E. A.; Hassan, M. A. E. (Journal of Phytopathology and Disease Management, 2014)
Root rot and wilt disease complex were detected in several guava, lemon and olive transplant nurseries and new orchards at El-Kharga, Baris, ballet, El-Dakhla and El-Farafrah districts, the New Valley Governorate, Egypt. The average percentage of root rot/wilt incidence and severity in surveying districts were 37.7, 26.5%in guava; 41.7, 34.0%;in lemon and 41.2, 29.5% in olive transplants, respectively. The most frequently isolated fungi from rotted roots of the guava, lemon and olive transplants were Fusarium oxysporum, F. solani, Macrophomina phaseolina and Rhizoctonia solani. In pathogenicity tests, all the tested fungi were pathogenic to guava, lemon and olive transplants. The effect of plant growth promoting rhizobacteria (PGPR) individually and/or mixed when used as a soil drench treatment were varied in reducing root rot/ wilt incidence and severity under greenhouse conditions compared with control. The mixed of PGPR gave the highest protection against root rot/wilt diseases compared with the use of PGPR individually. All treatments significantly increased plant height (cm), number of leaves transplanting-1, leaf area (cm2), fresh and dry weights transplanting-1 (gm) compared with control treatment.